Sociology Program MOU, Spring 2023 (2023)
The Sociology Program has carefully reviewed and considered the assessment and recommendations of the External Reviewers and the Dean. The Program appreciates the recognition of the many strengths of the program. Using the template provided, the table below summarizes, in the first two columns, the recommendations and rationale that were submitted by the reviewers. The next four columns are the Program's responses. The Program has added the color coding to the template. The color coding in the first column indicates whether the Program will create steps to address the recommendations (green), the Program is unsure of either the capacity or willingness to address the recommendations (orange), the work is already ongoing (blue), or the decision of the Program not to proceed with the recommendation (red). In the case of the latter, the third column explains the rationale behind our decision not to pursue the recommendation. It is important to emphasize that the efforts to address the recommendations depend upon all faculty participating (at least TTF, with NTTF most welcome to do so if they choose) and upon the support from external parties as indicated. These conditions have not been present in recent years and may interfere with the completion of the below recommendations.